Species composition of the order Cantharellales in Tay Nguyen, Vietnam - Dung, Le Ba (Academia Journal of Biology, 2015)
There are 6 species belonging to 3 genera, 2 families Fistulinaceae and Cantharellaceae of the order Cantharellales in Taynguyen - the West Highland of Vietnam. Of the family Fistulinaceae, there is 1 species - Fistulina hepatica Schaeff. ex Fr. Of the family Cantharellaceae, there are 5 species belonging to 2 genera: Cantharellus Jusseus with 4 species: C. cibareus Fr., C. muscigenus Fr., C. tubaeformis Fr. and C. infundibuliformis Fr. and Craterellus Pers. with 1 species: Craterellus lutescens Fr. Among them, Craterellus lutescens Fr. is a new species for the West Highland macrofungi flora, and also a new species for the macrofungi flora of Vietnam.